Comprehensive identification and expression analysis of the TIFY gene family in cucumber - Juncheng HE; Yikeng CHENG; Lingdi XIAO; Zhaoyang HU; Yong ZHOU; Shiqiang LIU (Notulae Botanicae Horti Agrobotanici Cluj-Napoca, 2022)
The TIFY family, a plant-specific gene family with the conserved motif of TIF[F/Y]XG, plays important roles in plant growth, development and abiotic stress response. This family encodes four subfamilies of proteins, including ZIM-like (ZML), TIFY, PPD and JASMONATE ZIM-domain (JAZ). In this study, 17 TIFY family genes were identified in cucumber through genome-wide analysis, including one PPD, two TIFYs, four ZMLs, and 10 JAZs. Phylogenetic analysis revealed that TIFY proteins from cucumber and other plant species can be divided into seven groups, which were designated as TIFY, JAZ I–IV, ZML and PPD. An analysis of conserved domain distribution demonstrated that there are four other domains (Jas, CCT, PPD and GATA domains) in CsTIFY proteins. Tissue expression profiling of the CsTIFY genes revealed that some of them displayed development- and tissue-specific expression patterns. Expression analysis based on transcriptome data and qRT-PCR revealed that the expression levels of some cucumber TIFY genes were altered under multiple abiotic stresses. In addition, several CsJAZ genes were downregulated in cucumber plants under root-knot nematode (RKN) infection, suggesting that they negatively affect the resistance response of cucumber to RKN. Our findings lay a foundation for further functional studies of the TIFY family genes in cucumber.